PENGARUH KUALITAS PELAYANAN DAN KEMAMPUAN MANAJERIAL PENGURUS TERHADAP KEPUASAN ANGGOTA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) UNIVERSITAS RIAU - Rona Holong Sitohang; Caska '; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of the research is to find out the influence of service quality and managerial ability of the administrator to the customer satisfaction of Koperasi Pegawai Republik Indonesia University of Riau. This research is a quantitative research, with amount of population is 1.949 members and amount sample is 94 members. The method that used to gathering data is quisioner. Analysis data method uses descriptive analysis, multiple linier regression and classical assumption test. The result of the research shows there is influence of service quality and managerial ability of the administator to the customer satisfaction with significance value of 0,001. Partially, service quality has influence to the customer satisfaction with significance value of 0,038 and managerial ability has influence to the customer satisfaction with significance of 0,003. With good service quality and good managerial ability, so that will increase customer satisfaction.Keywords : Quality of Service , Managerial Ability , Customer Satisfaction .